Modified ternary positive electrode material and preparation method and application thereof

Through cobalt hydroxide coating and aluminum hydroxide/poly(TA) composite layer coating, the lithium diffusion and ionic conductivity of the positive electrode material of lithium-ion battery are improved, and the poor power performance of lithium-ion batteries at low temperatures is solved. Problem, excellent high-speed charging and discharging performance is achieved.

CN119263363AActive Publication Date: 2025-01-07HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411368379.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-07
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Lithium-ion batteries have poor power performance under low temperature conditions, resulting in too long charging time, and the low lithium diffusion and ionic conductivity of common positive electrode materials limit their application.

Method used

The preparation method of high-performance modified ternary cathode material is adopted, and the lithium diffusion and ionic conductivity of the material are improved by cobalt hydroxide coating, aluminum hydroxide/poly(TA) composite layer coating and polyurea modification treatment. Reduce polarization internal resistance.

Benefits of technology

The charging and discharging performance of lithium-ion batteries is significantly improved under low temperature conditions, and excellent large-scale charging and discharging capabilities and low polarization internal resistance are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005066885780000052
    Figure BDA0005066885780000052
  • Figure BDA0005066885780000061
    Figure BDA0005066885780000061
  • Figure BDA0005066885780000062
    Figure BDA0005066885780000062
Patent Text Reader

Abstract

The invention discloses a preparation method of a modified ternary positive electrode material. According to the method, a precursor dust collection material is coated and modified, and the sintering pressure is controlled to prepare the large and small particle mixed ternary positive electrode material with the small particle proportion of 20.8-31.2%; and coating the surface of the ternary positive electrode material with a polyurea modified aluminum hydroxide / poly (TA) composite layer to prepare the high-performance modified ternary positive electrode material. According to the prepared high-performance modified ternary positive electrode material, the lithium diffusion coefficient at the low temperature is effectively improved, the polarization internal resistance of a lithium ion battery at the low temperature is reduced, and the battery shows excellent high-rate charge-discharge performance under the low-temperature condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium-ion batteries, and in particular relates to a modified ternary positive electrode material and a preparation method and application thereof. Background Art

[0002] In the era of electric vehicles (EVs), lithium-ion batteries (LIBs) play a vital role. x Co y M 1-x-y (OH) 2 Positive electrode materials are the main positive electrode materials used in future electric vehicle batteries. However, with the rapid expansion of the electric vehicle market, problems related to electric vehicles have become increasingly prominent. One of the most serious problems is that the battery has poor power performance at low temperatures (<-5°C), resulting in a long charging time at low temperatures.

[0003] For a long time, in order to improve the low-temperature power performance of batteries, researchers have continuously increased the Ni content and reduced the Co content in the positive electrode materials, and modified the positive electrode materials with heterogeneous doping elements. However, the common intercalation-based composite positive electrode has limited its power performance at low temperatures due to its low lithium diffusion coefficient and poor reaction kinetics, which further limits its wide application at low temperatures.

[0004] Therefore, it is urgent to develop a Ni x Co y M 1-x-y (OH) 2 The ternary positive electrode material has high lithium diffusion and ion conductivity under low temperature conditions. The polarization internal resistance of the lithium-ion battery used in it does not increase significantly, and it exhibits excellent high-rate charge and discharge performance. Summary of the invention

[0005] In order to solve the technical problems that the above-mentioned positive electrode materials have poor lithium diffusion and ion conductivity under low temperature conditions, as well as the polarization internal resistance of the lithium ion batteries used therein increases significantly and the high-rate charge and discharge performance is poor, the present invention provides a preparation method and application of a high-performance modified ternary positive electrode material.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a high-performance modified ternary positive electrode material.

[0008] The method for preparing the high-performance modified ternary cathode material provided by the present invention comprises the following steps:

[0009] 1) mixing a ternary precursor, a cobalt hydroxide-coated ternary precursor, a dopant, and a lithium source, and sintering the mixed material to obtain an intermediate sample of a ternary positive electrode material;

[0010] 2) coating the surface of the intermediate sample of the ternary cathode material in step 1 with aluminum hydroxide, then reacting it with thioctic acid (TA) in the first step, and then adding solvent I to carry out the second step reaction to obtain an aluminum hydroxide / poly (TA) composite layer coated ternary cathode material; the solvent I is selected from at least one of dichloromethane, methanol, and chloroform;

[0011] 3) subjecting the aluminum hydroxide / poly (TA) composite layer coated ternary cathode material described in step 2 to low-temperature oxygen plasma surface treatment to obtain a modified aluminum hydroxide / poly (TA) composite layer coated ternary cathode material;

[0012] 4) The modified aluminum hydroxide layer and the poly (TA) film layer composite layer coated ternary positive electrode material described in step 3 are polymerized with diisocyanate and α, ω-diisocyanate polyethylene glycol to obtain a polyurea-modified aluminum hydroxide / poly (TA) composite layer coated modified ternary positive electrode material, which is the modified ternary positive electrode material.

[0013] In step 1 of the above method, preferably, the chemical formula of the ternary precursor is Ni x Co y M 1-x-y (OH) 2 , wherein 0<x<1, 0<y<1, 1-xy>0, M is at least one of Mn, Al,

[0014] According to one embodiment of the present invention, the chemical formula of the ternary precursor is Ni 0.7 Co 0.1 Al 0.2 (OH) 2 ;

[0015] According to one embodiment of the present invention, the chemical formula of the ternary precursor is Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 ;

[0016] According to one embodiment of the present invention, the chemical formula of the ternary precursor is Ni 0.9 Co 0.02 Mn 0.08 (OH) 2 ;

[0017] According to one embodiment of the present invention, the chemical formula of the ternary precursor is Ni 0.6 Co 0.2 Mn 0.2 (OH) 2 .

[0018] In step 1 of the above method, preferably, the lithium source is at least one of lithium hydroxide, lithium perchlorate, lithium hexafluorophosphate, and lithium carbonate; preferably, the dopant is at least one of tungstic acid, tungsten oxide, strontium carbonate, strontium oxide, aluminum oxide, zirconium oxide, niobium oxide, boric acid, vanadium dioxide, and molybdenum trioxide.

[0019] In step 1 of the above method, preferably, the particle size range of the ternary precursor is 1.2 to 9 μm; preferably, the particle size range of the cobalt hydroxide-coated ternary precursor is 1.3 to 6.8 μm.

[0020] In step 1 of the above method, preferably, the preparation method of the cobalt hydroxide coated ternary precursor comprises the following steps: taking the ternary precursor dust collection material and the coating agent I and adding them into a stirred reactor filled with deionized water, stirring and mixing at 100-300 r / min for 20-120 min to obtain slurry I, then adding the precipitant I to the slurry I to adjust the pH value to 9-11, aging at 30-65° C. for 4-16 h, and then filtering, washing, and drying to obtain the coated precursor;

[0021] More preferably, the coating agent I is cobalt sulfate; more preferably, the mass ratio of the ternary precursor dust collecting material, coating agent I, and deionized water is 1:0.01-0.05:3-5; more preferably, the precipitating agent I is ammonia water and / or sodium hydroxide.

[0022] In the above method, the ternary precursor dust material is the dust material collected during the ternary precursor feeding process. Preferably, the particle size of the precursor dust material ranges from 1.2 to 6.4 μm.

[0023] In step 1 of the above method, preferably, the mass ratio of the ternary precursor, the cobalt hydroxide-coated ternary precursor, the dopant, and the lithium source is (0.3-1):3:(0.0001-0.012):(1.43-1.92).

[0024] In step 1 of the above method, preferably, the sintering is carried out in a kiln, and the internal pressure of the kiln is set to 200-500 Pa during the sintering; the sintering temperature is 700-950° C., and the sintering time is 10-30 hours.

[0025] In step 1 of the above method, preferably, the total number of particles W with a particle size of 1.2 to 2.9 μm in the intermediate sample of the ternary positive electrode material is 1 Total number of particles W 0 The percentage is 20.8-31.2%; the particle ratio here is tested by Malvern MS3000 laser particle size analyzer to determine the particle size range of different particle sizes, and the target particle size ratio range is determined by the particle size test results of MS3000.

[0026] Preferably, the particle size distribution dispersion of the intermediate sample of the ternary positive electrode material is 2.4 to 4;

[0027] Preferably, the residual alkali (LiOH and Li 2 CO 3 ) wherein the mass proportion of lithium hydroxide is 0.1 to 0.25%, and the mass proportion of lithium carbonate is 0.1 to 0.2%.

[0028] In step 2 of the above method, preferably, the aluminum hydroxide coating method comprises the following steps: adding the intermediate sample of the ternary positive electrode material and the coating agent II into a stirred reactor filled with deionized water, stirring and mixing at 400-800 r / min for 60-120 min to obtain slurry II, then adding a precipitant II to the slurry II to adjust the pH value to 9-11, aging at 40-75° C. for 2-12 h, and then filtering, washing, and drying to obtain the slurry;

[0029] More preferably, the coating agent II is aluminum sulfate; more preferably, the mass ratio of the ternary positive electrode material intermediate sample, coating agent II, and deionized water is 1:0.03-0.06:5-8; more preferably, the precipitating agent II is ammonia water and / or sodium hydroxide.

[0030] In step 2 of the above method, preferably, the mass ratio of the aluminum hydroxide-coated ternary positive electrode material, thioctic acid (TA), and solvent I is (2066.46-25756.94): (3.6-25.76): 1; specifically, 3066.46: 6.8: 1, 18062.2: 16.8: 1, 2066.46: 3.6: 1, 4078.12: 13.6: 1, or 25756.94: 25.76: 1.

[0031] More preferably, the reaction temperature of the first step reaction is 100-120° C., the stirring speed is 50-100 r / min, and the stirring reaction time is 2-6 h; more preferably, the stirring reaction time of the second step reaction is 30-60 min.

[0032] In step 3 of the above method, preferably, the low-temperature oxygen plasma surface treatment is carried out in a low-temperature plasma surface treatment machine. Before the treatment, the low-temperature plasma surface treatment machine needs to be evacuated, and then a certain amount of oxygen is introduced into the treatment machine to reach the required treatment pressure; more preferably, the vacuum degree of the evacuation is 5 to 10 Pa; more preferably, the treatment pressure is 20 to 100 Pa.

[0033] In step 3 of the above method, preferably, the step of low-temperature oxygen plasma surface treatment is: setting the frequency of the low-temperature oxygen plasma surface treatment machine to 10-40 Hz, setting the input power to 200-800 W, fixing the spray gun nozzle to 10-15 mm from the sample, and using a bow-shaped reciprocating treatment for 5-25 s.

[0034] In step 4 of the above method, preferably, the polymerization is carried out in a reaction solution, and the reaction solution is obtained by stirring and mixing the diisocyanate, the α,ω-diisocyanate polyethylene glycol and the solvent II in a mass ratio of 1:0.21 to 0.34:0.5;

[0035] More preferably, the α,ω-diisocyanate polyethylene glycol has the following structural formula: 500≤n≤1000;

[0036] More preferably, the diisocyanate is at least one of toluene diisocyanate, diphenylmethane diisocyanate, and 1,5-naphthalene diisocyanate;

[0037] More preferably, the solvent II is acetone and / or N,N-dimethylformamide.

[0038] More preferably, the mass ratio of the modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material to the reaction solution is 1:0.17-0.24.

[0039] In step 4 of the above method, the polymerization reaction is a two-step temperature polymerization, that is, a stirring reaction is first performed, and then a second stirring reaction is performed after the reaction temperature is lowered; preferably, the first stirring reaction and the second stirring reaction are both performed in a plowshare dryer.

[0040] More preferably, the primary stirring reaction is to maintain the internal temperature of the plowshare dryer cavity at 110-130°C through a heat transfer medium, set the spindle speed to 100-200r / min, and the reaction time to 30-60min; more preferably, the secondary stirring reaction is to maintain the internal temperature of the plowshare dryer cavity at 30-50°C through a heat transfer medium, set the spindle speed to 50-100r / min, and the reaction time to 1-2h.

[0041] In the second aspect, the present invention also protects the high-performance modified ternary positive electrode material prepared by the above method.

[0042] In a third aspect, the present invention also protects the application of the high-performance modified ternary positive electrode material prepared by the above method.

[0043] The application is the application of the high-performance modified ternary positive electrode material in the preparation of lithium-ion batteries.

[0044] In a fourth aspect, the present invention protects a lithium ion battery.

[0045] The lithium-ion battery comprises a positive electrode, a negative electrode, a separator and an electrolyte, and the material of the positive electrode comprises the above-mentioned high-performance modified ternary positive electrode material.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] 1) The present invention coats the dust collected during the precursor feeding process with cobalt hydroxide, and then mixes it with the uncollected precursor, dopant, and lithium source in a certain proportion, and sinters it in one step to obtain an intermediate sample of the ternary positive electrode material. In the above preparation method, the present invention coats the dust precursor with cobalt hydroxide, and the cobalt doping during the sintering process can effectively promote the growth of the primary particles of the dust precursor. The high furnace pressure sintering conditions and the synergistic effect of the dopant are set to make the small and medium particles (particles with a particle size of 1.2 to 2.9 μm) of the intermediate sample of the ternary positive electrode material reach 20.8 to 31.2%. The mixing of large and small primary particles synergistically balances the electrochemical reaction differences of the primary particles of the intermediate sample of the ternary positive electrode material, and effectively inhibits the cation reduction of the transition metal layer.

[0048] 2) The present invention selectively uses solvents such as dichloromethane, methanol and chloroform, and adopts a heating and stirring method to simply and effectively construct a layer of poly (TA) film on the surface of the intermediate sample of the ternary positive electrode material. Through the selection of the reaction solvent, the constructed poly (TA) film layer has excellent flexibility and ductility under high and low temperature environments, which can effectively reduce interfacial side reactions and improve the lithium diffusion and ion conductivity of the material under low temperature conditions.

[0049] 3) The present invention constructs a hydroxyl group-modified aluminum hydroxide layer outside the poly (TA) film layer through hydrolysis and low-temperature oxygen plasma modification technology. The modified aluminum hydroxide layer and the poly (TA) film layer can effectively slow down the precipitation of lattice oxygen under long-cycle conditions of the ternary positive electrode material to produce NiO phase and oxygen-containing byproduct Li 2 O, effectively improving the long cycle performance of the lithium-ion battery under high and low temperature conditions.

[0050] 4) In addition, the present invention also prepares a polyurea-modified aluminum hydroxide / poly (TA) composite layer-coated modified ternary positive electrode material by subjecting the modified aluminum hydroxide layer and the poly (TA) film layer composite layer to two step-type temperature polymerizations with diisocyanate and α, ω-diisocyanate-based polyethylene glycol. The addition of diisocyanate and α, ω-diisocyanate-based polyethylene glycol and the synergistic effect of two step-type temperature polymerizations reduce the rigidity of the polyurea segment, effectively improve the lithium diffusion and ionic conductivity of the material under low temperature conditions, and the polarization internal resistance of the applied lithium-ion battery does not increase significantly, showing excellent high-rate charge and discharge performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is a microscopic morphology image of Example 1 at 10,000 times magnification;

[0052] Figure 2 This is a microscopic morphology image of comparative example 1 magnified 10,000 times. DETAILED DESCRIPTION

[0053] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0054] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0055] The α,ω-diisocyanate polyethylene glycol used in the following examples has the following structural formula:

[0056] 500≤n≤1000.

[0057] The residual alkali test method in the following embodiments is as follows: weigh the sample according to the table below, accurate to 0.0001g, place the weighed sample in a 100mL beaker, add 50mL of deionized water, put the magnetic beads in the beaker and seal it with plastic wrap, then place the beaker on a magnetic stirrer and stir for about 10-15min and remove it; let it stand for 5min, filter it with a glass funnel, and the filtered clear liquid is the test solution.

[0058] Table 1 Residual alkali test method

[0059]

[0060] Accurately transfer the solution to be tested into a 100mL beaker, put in a stirring rotor, control the sample volume to about 50mL (make up with water if less than 50mL), place the beaker on the magnetic stirrer of the automatic potentiometric titrator, add phenolphthalein for 2d, select HCl standard solution according to the table and titrate it from red to colorless. The instrument will record the volume Ep1(V1) of HCl standard solution consumed at the stoichiometric point and the pH; then add methyl orange for 2d, continue to titrate it from yellow to orange. The instrument will record the volume Ep2(V2) of HCl standard solution consumed at the stoichiometric point and the pH.

[0061] Analysis results calculation:

[0062] (1) When 2V1>V2, it contains LiOH and Li2CO3, and the calculation formula is as follows:

[0063]

[0064] (2) When 2V1<V2, Li 2 CO 3 、LiHCO 3 , the calculation formula is as follows:

[0065]

[0066] (3) When 2V1 = V2, only Li 2 CO 3 , the calculation formula is as follows:

[0067]

[0068] In the above formula: c: concentration of HCl standard solution (mol / L); V1(Ep1): volume of HCl standard solution consumed at the first equivalence point (mL); V2(Ep2): volume of HCl standard solution consumed at the second equivalence point (including the first equivalence point) (mL); V': volume of the sample solution (mL); V: volume of the sample solution (mL); 23.95: molar mass of LiOH (g / mol); 73.89: Li 2 CO 3 Molar mass g / mol; 67.96: LiHCO 3 Molar mass g / mol; m: mass of the sample (g).

[0069] Example 1

[0070] A method for preparing a high-performance modified ternary cathode material, the preparation steps of which are as follows:

[0071] 1. Preparation of intermediate samples of ternary cathode materials

[0072] (1) Preparation of cobalt hydroxide coated ternary precursor:

[0073] Take the ternary precursor dust collection material Ni 0.7 Co 0.1 Mn 0.2 (OH) 2 (particle size 1.2-6.4 μm) and cobalt sulfate were added to a stirred reactor filled with deionized water, stirred and mixed at 300 r / min for 20 min to obtain slurry I, and then ammonia water was added to slurry I to adjust the pH value to 9-11, aged at 65 ° C for 16 h, and then filtered, washed and dried to obtain cobalt hydroxide-coated precursor Co(OH)2-Ni 0.7Co 0.1 Mn 0.2 (OH) 2 (particle size 1.3 ~ 6.8μm); in the above preparation method, the precursor dust collecting material Ni 0.7 Co 0.1 Mn 0.2 (OH) 2 , cobalt sulfate, and deionized water in a mass ratio of 1:0.01:5;

[0074] (2) Preparation of intermediate samples of ternary cathode materials:

[0075] The ternary precursor Ni 0.7 Co 0.1 Mn 0.2 (OH) 2 (particle size 1.2 ~ 9μm), coated ternary precursor Co(OH)2-Ni 0.7 Co 0.1 Mn 0.2 (OH) 2 , tungstic acid, and lithium hydroxide are mixed in a mass ratio of 0.3:3:0.012:1.43, and the internal pressure of the kiln is set to 500Pa and the temperature is set to 950℃ to sinter the mixed materials for 10 hours. After crushing and sieving, an intermediate sample of the ternary positive electrode material is obtained; among which, the total number of particles with a particle size of 1.2 to 2.9μm in the intermediate sample of the ternary positive electrode material is W 1 Total number of particles W 0 The percentage of the obtained material is 31.2%, the particle size distribution dispersion ((D90-D10) / D50) is 4, and the residual alkali in the obtained material is: lithium hydroxide accounts for 0.25% by weight, and lithium carbonate accounts for 0.14% by weight. The residual alkali is determined by titration.

[0076] 2. Preparation of modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material

[0077] (1) Preparation of aluminum hydroxide coated ternary positive electrode material:

[0078] The intermediate sample of the ternary cathode material prepared in 1 and aluminum sulfate were added to a stirred reactor filled with deionized water, and the mixture was stirred at 800 r / min for 120 min to obtain slurry II, and then ammonia water was added to the slurry II to adjust the pH value to 9-11, and the slurry was aged at 75° C. for 5 h, and then filtered, washed, and dried to obtain slurry II; in the above preparation method, the mass ratio of the ternary cathode material, aluminum sulfate, and deionized water was 1:0.05:5;

[0079] (2) Preparation of aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material:

[0080] Aluminum hydroxide coated ternary cathode material and thioctic acid (TA) were added to a reactor at the same time, the reaction temperature was set to 105°C, the stirring speed was 80 r / min, and the reaction was stirred for 5.5 hours, and then dichloromethane was added and the stirring reaction was continued for 60 minutes, and then the temperature was cooled to room temperature to obtain an aluminum hydroxide / poly (TA) composite layer coated ternary cathode material; in the above preparation method, the mass ratio of the aluminum hydroxide coated ternary cathode material intermediate sample, thioctic acid (TA), and dichloromethane was 3066.46:6.8:1;

[0081] (3) Preparation of modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material

[0082] The low-temperature plasma surface treatment machine is evacuated to a vacuum degree of 10Pa, and then a certain amount of oxygen is introduced into the treatment machine to make the treatment pressure reach 24Pa, and an aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is added thereto for low-temperature oxygen plasma surface treatment to obtain a modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material; in the above preparation method, the low-temperature oxygen plasma surface treatment step is: setting the frequency of the low-temperature oxygen plasma surface treatment machine to 19Hz, setting the input power to 560W, fixing the spray gun nozzle to 10mm away from the sample, and using a bow-shaped reciprocating treatment for 12s.

[0083] 3. Preparation of high-performance modified ternary cathode materials

[0084] The internal temperature of the plowshare dryer cavity is maintained at 120°C by circulating heating oil, the main shaft speed is set to 120r / min, and the modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is added to the reaction liquid and stirred for 60 minutes, and then the internal temperature of the plowshare dryer cavity is maintained at 42°C by reducing the temperature of the circulating heating oil, the main shaft speed is set to 82r / min, and the stirring reaction time is continued for 1.5 hours. After cooling to room temperature, the polyurea modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is obtained by sieving and demagnetizing, which is the high-performance positive electrode material; in the above preparation method, the mass ratio of the modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material to the reaction liquid is 1:0.2; the reaction liquid is obtained by stirring and mixing toluene diisocyanate, α, ω-diisocyanate polyethylene glycol, and acetone in a mass ratio of 1:0.24:0.5.

[0085] Example 2

[0086] A method for preparing a high-performance modified ternary cathode material, the preparation steps of which are as follows:

[0087] 1. Preparation of intermediate samples of ternary cathode materials

[0088] (1) Preparation of cobalt hydroxide coated ternary precursor:

[0089] Take the ternary precursor dust collection material Ni0.7 Co 0.1 Al 0.2 (OH) 2 (particle size 1.3 ~ 6μm), cobalt sulfate was added to a stirred reactor filled with deionized water, stirred and mixed at 140r / min for 80min to obtain slurry I, and then ammonia water was added to slurry I to adjust the pH value to 9-11, aged at 50°C for 10h, and then filtered, washed and dried to obtain cobalt hydroxide-coated precursor Co(OH)2-Ni 0.7 Co 0.1 Al 0.2 (OH) 2 (particle size 1.4 ~ 6.5μm); in the above preparation method, the precursor dust collecting material Ni 0.7 Co 0.1 Al 0.2 (OH) 2 , cobalt sulfate, and deionized water in a mass ratio of 1:0.04:3;

[0090] (2) Preparation of intermediate samples of ternary cathode materials:

[0091] The ternary precursor Ni 0.7 Co 0.1 Al 0.2 (OH) 2 (particle size 1.3 ~ 8μm), coated ternary precursor Co(OH)2-Ni 0.7 Co 0.1 Al 0.2 (OH) 2 , strontium carbonate, and lithium hexafluorophosphate are mixed in a mass ratio of 0.4:3:0.012:1.63, and the internal pressure of the kiln is set to 300Pa and the temperature is set to 800℃ to sinter the mixed materials for 15h. After crushing and sieving, an intermediate sample of the ternary positive electrode material is obtained; among which, the total number of particles with a particle size of 1.2 to 2.9μm in the intermediate sample of the ternary positive electrode material is W 1 Total number of particles W 0 The percentage is 21.4%, the particle size distribution dispersion is 3.2, and the residual alkali in the obtained material: lithium hydroxide accounts for 0.18% by mass, and lithium carbonate accounts for 0.1% by mass.

[0092] 2. Preparation of modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material

[0093] (1) Preparation of aluminum hydroxide coated ternary positive electrode material:

[0094] The intermediate sample of the ternary cathode material prepared in 1 and aluminum sulfate were added to a stirred reactor filled with deionized water, and the mixture was stirred at 600 r / min for 80 min to obtain slurry II, and then sodium hydroxide was added to the slurry II to adjust the pH value to 9-11, and the slurry was aged at 62° C. for 3.8 h, and then filtered, washed, and dried to obtain slurry II; in the above preparation method, the mass ratio of the ternary cathode material, aluminum sulfate, and deionized water was 1:0.04:6.5;

[0095] (2) Preparation of aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material:

[0096] The aluminum hydroxide coated ternary cathode material and thioctic acid (TA) were added to a reactor at the same time, the reaction temperature was set to 110°C, the stirring speed was 66 r / min, and the reaction was stirred for 2.5 hours, and then methanol was added and the stirring reaction was continued for 50 minutes, and then the temperature was cooled to room temperature to obtain an aluminum hydroxide / poly (TA) composite layer coated ternary cathode material; in the above preparation method, the mass ratio of the aluminum hydroxide coated ternary cathode material intermediate sample, thioctic acid (TA), and methanol was 18062.2:16.8:1;

[0097] (3) Preparation of modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material

[0098] The low-temperature plasma surface treatment machine is evacuated to a vacuum degree of 8Pa, and then a certain amount of oxygen is introduced into the treatment machine to make the treatment pressure reach 60Pa, and an aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is added thereto for low-temperature oxygen plasma surface treatment to obtain a modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material; in the above preparation method, the low-temperature oxygen plasma surface treatment step is: setting the frequency of the low-temperature oxygen plasma surface treatment machine to 32Hz, setting the input power to 660W, fixing the spray gun nozzle to 12mm away from the sample, and using a bow-shaped reciprocating treatment for 10s.

[0099] 3. Preparation of high-performance ternary cathode materials

[0100] The internal temperature of the coulter dryer cavity is maintained at 112°C by circulating heating oil, the main shaft speed is set to 105r / min, and the modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is added to the reaction liquid for stirring and reacting for 40 minutes, and then the internal temperature of the coulter dryer cavity is maintained at 45°C by reducing the temperature of the circulating heating oil, the main shaft speed is set to 90r / min, and the stirring reaction time is continued for 1.2h. After cooling to room temperature, the polyurea modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is obtained by sieving and demagnetizing, which is the high-performance positive electrode material; in the above preparation method, the mass ratio of the modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material to the reaction liquid is 1:0.22; the reaction liquid is obtained by stirring and mixing diphenylmethane diisocyanate, α, ω-diisocyanate polyethylene glycol, and N,N-dimethylformamide in a mass ratio of 1:0.3:0.5.

[0101] Example 3

[0102] A method for preparing a high-performance modified ternary cathode material, the preparation steps of which are as follows:

[0103] 1. Preparation of intermediate samples of ternary cathode materials

[0104] (1) Preparation of cobalt hydroxide coated ternary precursor:

[0105] Take the ternary precursor dust collection material Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 (particle size 1.4-6 μm) and cobalt sulfate were added to a stirred reactor filled with deionized water, stirred and mixed at 100 r / min for 20 min to obtain slurry I, and then ammonia water was added to slurry I to adjust the pH value to 9-11, aged at 30 ° C for 4 h, and then filtered, washed and dried to obtain cobalt hydroxide-coated precursor Co(OH)2-Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 (particle size 1.4 ~ 6μm); in the above preparation method, the precursor dust collecting material Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 , cobalt sulfate, and deionized water in a mass ratio of 1:0.01:3;

[0106] (2) Preparation of intermediate samples of ternary cathode materials:

[0107] The ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2(particle size 1.5 ~ 8μm), coated with ternary precursor Co(OH)2-Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 , strontium oxide, and lithium carbonate are mixed in a mass ratio of 0.3:3:0.012:1.43, and the internal pressure of the kiln is set to 200Pa and the temperature is set to 700℃ to sinter the mixed materials for 10 hours. After crushing and sieving, an intermediate sample of the ternary positive electrode material is obtained; among which, the total number of particles with a particle size of 1.2 to 2.9μm in the intermediate sample of the ternary positive electrode material is W 1 Total number of particles W 0 The percentage is 20.8%, the particle size distribution dispersion is 2.4, and the residual alkali in the obtained material: lithium hydroxide accounts for 0.1% by mass, and lithium carbonate accounts for 0.1% by mass.

[0108] 2. Preparation of modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material

[0109] (1) Preparation of aluminum hydroxide coated ternary positive electrode material:

[0110] The intermediate sample of the ternary cathode material prepared in 1 and aluminum sulfate are added to a stirred reactor filled with deionized water, and the mixture is stirred at 400 r / min for 60 min to obtain slurry II, and then sodium hydroxide is added to the slurry II to adjust the pH value to 9-11, and the slurry is aged at 40° C. for 2 h, and then filtered, washed, and dried to obtain slurry II; in the above preparation method, the mass ratio of the intermediate sample of the ternary cathode material, aluminum sulfate, and deionized water is 1:0.03:5;

[0111] (2) Preparation of aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material:

[0112] Aluminum hydroxide coated ternary cathode material and thioctic acid (TA) were added to a reactor at the same time, the reaction temperature was set to 100°C, the stirring speed was 50 r / min, and the reaction was stirred for 2 hours, and then chloroform was added and the stirring reaction was continued for 30 minutes, and then the temperature was cooled to room temperature to obtain an aluminum hydroxide / poly (TA) composite layer coated ternary cathode material; in the above preparation method, the mass ratio of aluminum hydroxide coated ternary cathode material, thioctic acid (TA), and chloroform was 2066.46:3.6:1;

[0113] (3) Preparation of modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material

[0114] The low-temperature plasma surface treatment machine is evacuated to a vacuum degree of 5Pa, and then a certain amount of oxygen is introduced into the treatment machine to make the treatment pressure reach 20Pa, and an aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is added thereto for low-temperature oxygen plasma surface treatment to obtain a modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material; in the above preparation method, the low-temperature oxygen plasma surface treatment step is: setting the frequency of the low-temperature oxygen plasma surface treatment machine to 10Hz, setting the input power to 200W, fixing the spray gun nozzle to 10mm away from the sample, and using a bow-shaped reciprocating treatment for 5s.

[0115] 3. Preparation of high-performance ternary cathode materials

[0116] The internal temperature of the coulter dryer cavity is maintained at 110°C by circulating heating oil, the main shaft speed is set to 100r / min, and the modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is added to the reaction liquid for stirring and reacting for 30 minutes, and then the internal temperature of the coulter dryer cavity is maintained at 30°C by reducing the temperature of the circulating heating oil, the main shaft speed is set to 50r / min, and the stirring reaction time is continued for 1 hour. After cooling to room temperature, the polyurea modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is obtained by sieving and demagnetizing, which is the high-performance positive electrode material; in the above preparation method, the mass ratio of the modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material to the reaction liquid is 1:0.17; the reaction liquid is obtained by stirring and mixing 1,5-naphthalene diisocyanate, α,ω-diisocyanate polyethylene glycol, and acetone in a mass ratio of 1:0.21:0.5.

[0117] Example 4

[0118] A method for preparing a high-performance ternary cathode material, the preparation steps of which are as follows:

[0119] 1. Preparation of intermediate samples of ternary cathode materials

[0120] (1) Preparation of cobalt hydroxide coated ternary precursor:

[0121] Take the ternary precursor dust collection material Ni 0.9 Co 0.02 Mn 0.08 (OH) 2 (particle size 1.2-5 μm) and cobalt sulfate were added to a stirred reactor filled with deionized water, stirred and mixed at 124 r / min for 72 min to obtain slurry I, and then sodium hydroxide was added to slurry I to adjust the pH value to 9-11, aged at 55 ° C for 8.4 h, and then filtered, washed and dried to obtain cobalt hydroxide-coated precursor Co(OH)2-Ni 0.9 Co 0.02 Mn 0.08 (OH) 2(particle size 1.3 ~ 5.5μm); in the above preparation method, the precursor dust collecting material Ni 0.9 Co 0.02 Mn 0.08 (OH) 2 , cobalt sulfate, and deionized water in a mass ratio of 1:0.027:4.2;

[0122] (2) Preparation of intermediate samples of ternary cathode materials:

[0123] The ternary precursor Ni 0.9 Co 0.02 Mn 0.08 (OH) 2 (particle size 1.2 ~ 9μm), coated ternary precursor Co(OH)2-Ni 0.9 Co 0.02 Mn 0.08 (OH) 2 , zirconium oxide, and lithium perchlorate are mixed in a mass ratio of 0.78:3:0.0016:1.73, and the internal pressure of the kiln is set to 340Pa and the temperature is set to 880℃ to sinter the mixed materials for 18h. After crushing and sieving, an intermediate sample of the ternary positive electrode material is obtained; among which, the total number of particles with a particle size of 1.2 to 2.9μm in the intermediate sample of the ternary positive electrode material is W 1 Total number of particles W 0 The percentage is 28.8%, the particle size distribution dispersion is 3.7, and the residual alkali in the obtained material: lithium hydroxide accounts for 0.192% by mass, and lithium carbonate accounts for 0.184% by mass.

[0124] 2. Preparation of modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material

[0125] (1) Preparation of aluminum hydroxide coated ternary positive electrode material:

[0126] The intermediate sample of the ternary positive electrode material prepared in 1 and aluminum sulfate were added to a stirred reactor filled with deionized water, and the mixture was stirred at 640 r / min for 105 min to obtain slurry II, and then ammonia water was added to the slurry II to adjust the pH value to 9-11, and the slurry was aged at 72° C. for 12 h, and then filtered, washed, and dried to obtain slurry II; in the above preparation method, the mass ratio of the intermediate sample of the ternary positive electrode material, aluminum sulfate, and deionized water was 1:0.043:5.8;

[0127] (2) Preparation of aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material:

[0128] Aluminum hydroxide coated ternary cathode material and thioctic acid (TA) were added to a reactor at the same time, the reaction temperature was set to 118°C, the stirring speed was 87 r / min, and the reaction was stirred for 4.2 hours, and then dichloromethane was added and the stirring reaction was continued for 45 minutes, and then the temperature was cooled to room temperature to obtain an aluminum hydroxide / poly (TA) composite layer coated ternary cathode material; in the above preparation method, the mass ratio of aluminum hydroxide coated ternary cathode material, thioctic acid (TA), and dichloromethane was 4078.12:13.6:1;

[0129] (3) Preparation of modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material

[0130] The low-temperature plasma surface treatment machine was evacuated to a vacuum degree of 6.4 Pa, and then a certain amount of oxygen was introduced into the treatment machine to make the treatment pressure reach 68 Pa, and an aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material was added thereto for low-temperature oxygen plasma surface treatment to obtain a modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material; in the above preparation method, the low-temperature oxygen plasma surface treatment step is: setting the frequency of the low-temperature oxygen plasma surface treatment machine to 38 Hz, setting the input power to 720 W, fixing the spray gun nozzle to 12.8 mm from the sample, and using a bow-shaped reciprocating treatment for 24 seconds.

[0131] 3. Preparation of high-performance ternary cathode materials

[0132] The internal temperature of the plowshare dryer cavity is maintained at 121°C by circulating heating oil, the main shaft speed is set to 118r / min, and the modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is added to the reaction liquid and stirred for reaction for 53min, and then the internal temperature of the plowshare dryer cavity is maintained at 38°C by reducing the temperature of the circulating heating oil, the main shaft speed is set to 85r / min, and the stirring reaction time is continued for 1.8h. After cooling to room temperature, the polyurea modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is obtained by sieving and demagnetizing, which is the high-performance positive electrode material; in the above preparation method, the mass ratio of the modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material to the reaction liquid is 1:0.21; the reaction liquid is obtained by stirring and mixing diphenylmethane diisocyanate, α,ω-diisocyanate polyethylene glycol, and acetone in a mass ratio of 1:0.28:0.5.

[0133] Example 5

[0134] A method for preparing a high-performance modified ternary cathode material, the preparation steps of which are as follows:

[0135] 1. Preparation of intermediate samples of ternary cathode materials

[0136] (1) Preparation of cobalt hydroxide coated ternary precursor:

[0137] Take the ternary precursor dust collection material Ni0.6 Co 0.2 Mn 0.2 (OH) 2 (particle size 1.5-5 μm), cobalt sulfate was added into a stirred reactor filled with deionized water, stirred and mixed at 300 r / min for 120 min to obtain slurry I, and then sodium hydroxide was added to slurry I to adjust the pH value to 9-11, aged at 65 ° C for 16 h, and then filtered, washed and dried to obtain cobalt hydroxide-coated precursor Co(OH)2-Ni 0.6 Co 0.2 Mn 0.2 (OH) 2 (particle size 1.55 ~ 5.5μm); in the above preparation method, the precursor dust collecting material Ni 0.6 Co 0.2 Mn 0.2 (OH) 2 , cobalt sulfate, and deionized water in a mass ratio of 1:0.05:5;

[0138] (2) Preparation of intermediate samples of ternary cathode materials:

[0139] The ternary precursor Ni 0.6 Co 0.2 Mn 0.2 (OH) 2 (particle size 1.2 ~ 8μm), coated ternary precursor Co(OH)2-Ni 0.6 Co 0.2 Mn 0.2 (OH) 2 , molybdenum trioxide, and lithium perchlorate are mixed in a mass ratio of 1:3:0.0001:1.92, and the internal pressure of the kiln is set to 500Pa and the temperature is set to 950℃ to sinter the mixed materials for 30h. After crushing and sieving, an intermediate sample of the ternary positive electrode material is obtained; wherein, the total number of particles with a particle size of 1.2 to 2.9μm in the intermediate sample of the ternary positive electrode material is W 1 Total number of particles W 0 The percentage is 31.2%, the particle size distribution dispersion is 4, and the residual alkali in the obtained material: lithium hydroxide accounts for 0.25% by mass, and lithium carbonate accounts for 0.2% by mass.

[0140] 2. Preparation of modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material

[0141] (1) Preparation of aluminum hydroxide coated ternary positive electrode material:

[0142] The intermediate sample of the ternary positive electrode material prepared in 1 and aluminum sulfate are added to a stirred reactor filled with deionized water, and stirred and mixed at 800 r / min for 120 min to obtain slurry II, and then ammonia water is added to the slurry II to adjust the pH value to 9-11, and aged at 75°C for 12 h, and then filtered, washed, and dried to obtain; in the above preparation method, the mass ratio of the intermediate sample of the ternary positive electrode material, aluminum sulfate, and deionized water is 1:0.06:8;

[0143] (2) Preparation of aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material:

[0144] Aluminum hydroxide coated ternary cathode material and thioctic acid (TA) are added to a reactor at the same time, the reaction temperature is set to 120°C, the stirring speed is 100 r / min, and the reaction is stirred for 6 hours, and then dichloromethane is added and the stirring reaction is continued for 60 minutes, and then the temperature is cooled to room temperature to obtain an aluminum hydroxide / poly (TA) composite layer coated ternary cathode material; in the above preparation method, the mass ratio of aluminum hydroxide coated ternary cathode material, thioctic acid (TA), and dichloromethane is 25756.94:25.76:1;

[0145] (3) Preparation of modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material

[0146] The low-temperature plasma surface treatment machine is evacuated to a vacuum degree of 10Pa, and then a certain amount of oxygen is introduced into the treatment machine to make the treatment pressure reach 100Pa, and an aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is added thereto for low-temperature oxygen plasma surface treatment to obtain a modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material; in the above preparation method, the low-temperature oxygen plasma surface treatment step is: setting the frequency of the low-temperature oxygen plasma surface treatment machine to 40Hz, setting the input power to 800W, fixing the spray gun nozzle to 15mm away from the sample, and using a bow-shaped reciprocating treatment for 25s.

[0147] 3. Preparation of high-performance ternary cathode materials

[0148] The internal temperature of the plowshare dryer cavity is maintained at 130°C by circulating heating oil, the main shaft speed is set to 200r / min, and the modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is added to the reaction liquid for stirring and reacting for 60min, and then the internal temperature of the plowshare dryer cavity is maintained at 50°C by lowering the temperature of the circulating heating oil, the main shaft speed is set to 100r / min, and the stirring reaction time is continued for 2h. After cooling to room temperature, the polyurea modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is obtained by sieving and demagnetizing, which is the high-performance positive electrode material; in the above preparation method, the mass ratio of the modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material to the reaction liquid is 1:0.24; the reaction liquid is obtained by stirring and mixing diphenylmethane diisocyanate, α,ω-diisocyanate polyethylene glycol, and acetone in a mass ratio of 1:0.34:0.5.

[0149] Comparative Example 1

[0150] This comparative example provides a positive electrode material with mixed large and small particles, and the specific preparation steps are as follows:

[0151] (1) Preparation of cobalt hydroxide coated ternary precursor:

[0152] Take the ternary precursor dust collection material Ni 0.7 Co 0.1 Mn 0.2 (OH) 2 (particle size 1.0-6.4 μm) and cobalt sulfate were added to a stirred reactor filled with deionized water, stirred and mixed at 300 r / min for 20 min to obtain slurry I, and then ammonia water was added to slurry I to adjust the pH value to 9-11, aged at 65 ° C for 16 h, and then filtered, washed and dried to obtain cobalt hydroxide-coated precursor Co(OH)2-Ni 0.7 Co 0.1 Mn 0.2 (OH) 2 (particle size 1.1 ~ 6.8μm); in the above preparation method, the precursor dust collecting material Ni 0.7 Co 0.1 Mn 0.2 (OH) 2 , cobalt sulfate, and deionized water in a mass ratio of 1:0.01:5;

[0153] (2) Preparation of ternary positive electrode materials:

[0154] The ternary precursor Ni 0.7 Co 0.1 Mn 0.2 (OH) 2 (particle size 1.1 ~ 9μm), coated with ternary precursor Co(OH)2-Ni 0.7 Co 0.1Mn 0.2 (OH) 2 , tungstic acid, and lithium hydroxide were mixed in a mass ratio of 0.3:1:0.012:1.43, and the internal pressure of the kiln was set to 500Pa and the temperature was set to 950℃ to sinter the mixed materials for 10 hours. After crushing and sieving, the ternary positive electrode material was obtained; wherein, the total number of particles W with a particle size of 1.2 to 2.9μm in the ternary positive electrode material 1 Total number of particles W 0 The percentage is 31.2%, the particle size distribution dispersion is 4, the mass proportion of lithium hydroxide is 0.25%, and the mass proportion of lithium carbonate is 0.14%.

[0155] Comparative Example 2

[0156] A method for preparing a high-performance modified ternary cathode material, the preparation steps of which are as follows:

[0157] 1. Preparation of intermediate samples of ternary cathode materials

[0158] (1) Preparation of cobalt hydroxide coated ternary precursor:

[0159] Take the ternary precursor dust collection material Ni 0.7 Co 0.1 Al 0.2 (OH) 2 (particle size 1.3 ~ 6μm), cobalt sulfate was added to a stirred reactor filled with deionized water, stirred and mixed at 140r / min for 80min to obtain slurry I, and then ammonia water was added to slurry I to adjust the pH value to 9-11, aged at 50°C for 10h, and then filtered, washed and dried to obtain cobalt hydroxide-coated precursor Co(OH)2-Ni 0.7 Co 0.1 Al 0.2 (particle size 1.4 ~ 6.5μm); in the above preparation method, the precursor dust collecting material Ni 0.7 Co 0.1 Al 0.2 (OH) 2 , cobalt sulfate, and deionized water in a mass ratio of 1:0.04:3;

[0160] (2) Preparation of intermediate samples of ternary cathode materials:

[0161] The ternary precursor Ni 0.7 Co 0.1 Al 0.2 (OH) 2 (particle size 1.3 ~ 8μm), coated ternary precursor Co(OH)2-Ni 0.7 Co 0.1 Al 0.2 (OH) 2, strontium carbonate, and lithium hexafluorophosphate are mixed in a mass ratio of 0.4:3:0.012:1.63, and the internal pressure of the kiln is set to 300Pa and the temperature is set to 800℃ to sinter the mixed materials for 15h. After crushing and sieving, an intermediate sample of the ternary positive electrode material is obtained; among which, the total number of particles with a particle size of 1.2 to 2.9μm in the intermediate sample of the ternary positive electrode material is W 1 Total number of particles W 0 The percentage is 21.4%, the particle size distribution dispersion is 3.2, and the residual alkali in the obtained material: lithium hydroxide accounts for 0.18% by mass, and lithium carbonate accounts for 0.1% by mass.

[0162] 2. Preparation of modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material

[0163] (1) Preparation of aluminum hydroxide coated ternary positive electrode material:

[0164] The intermediate sample of the ternary cathode material prepared in 1 and aluminum sulfate were added to a stirred reactor filled with deionized water, and the mixture was stirred at 600 r / min for 80 min to obtain slurry II, and then sodium hydroxide was added to the slurry II to adjust the pH value to 9-11, and the slurry was aged at 62° C. for 3.8 h, and then filtered, washed, and dried to obtain slurry II; in the above preparation method, the mass ratio of the ternary cathode material, aluminum sulfate, and deionized water was 1:0.04:6.5;

[0165] (2) Preparation of aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material:

[0166] Aluminum hydroxide coated ternary cathode material and thioctic acid (TA) were added to a reactor at the same time, the reaction temperature was set to 110°C, the stirring speed was 66 r / min, and the reaction was stirred for 2.5 hours, and then methanol was added and the stirring reaction was continued for 50 minutes, and then the temperature was cooled to room temperature to obtain an aluminum hydroxide / poly (TA) composite layer coated ternary cathode material; in the above preparation method, the mass ratio of aluminum hydroxide coated ternary cathode material, thioctic acid (TA), and methanol was 18062.2:16.8:1;

[0167] (3) Preparation of modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material

[0168] The low-temperature plasma surface treatment machine is evacuated to a vacuum degree of 8Pa, and then a certain amount of oxygen is introduced into the treatment machine to make the treatment pressure reach 60Pa, and an aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material is added thereto for low-temperature oxygen plasma surface treatment to obtain a modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material; in the above preparation method, the low-temperature oxygen plasma surface treatment step is: setting the frequency of the low-temperature oxygen plasma surface treatment machine to 32Hz, setting the input power to 660W, fixing the spray gun nozzle to 12mm away from the sample, and using a bow-shaped reciprocating treatment for 10s.

[0169] Comparative Example 3

[0170] A method for preparing a high-performance ternary cathode material, the preparation steps of which are as follows:

[0171] 1. Preparation of intermediate samples of ternary cathode materials

[0172] (1) Preparation of cobalt hydroxide coated ternary precursor:

[0173] Take the ternary precursor dust collection material Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 (particle size 1.4-6 μm) and cobalt sulfate were added to a stirred reactor filled with deionized water, stirred and mixed at 100 r / min for 20 min to obtain slurry I, and then ammonia water was added to slurry I to adjust the pH value to 9-11, aged at 30 ° C for 4 h, and then filtered, washed and dried to obtain cobalt hydroxide-coated precursor Co(OH)2-Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 (particle size 1.4 ~ 6μm); in the above preparation method, the precursor dust collecting material Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 , cobalt sulfate, and deionized water in a mass ratio of 1:0.01:3;

[0174] (2) Preparation of intermediate samples of ternary cathode materials:

[0175] The ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 (particle size 1.5 ~ 8μm), coated with ternary precursor Co(OH)2-Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 , strontium oxide, and lithium carbonate are mixed in a mass ratio of 0.3:3:0.012:1.43, and the internal pressure of the kiln is set to 200Pa and the temperature is set to 700℃ to sinter the mixed materials for 10 hours. After crushing and sieving, an intermediate sample of the ternary positive electrode material is obtained; among which, the total number of particles with a particle size of 1.2 to 2.9μm in the intermediate sample of the ternary positive electrode material is W 1 Total number of particles W 0 The percentage is 20.8%, the particle size distribution dispersion is 2.4, and the residual alkali in the obtained material: lithium hydroxide accounts for 0.1% by mass, and lithium carbonate accounts for 0.1% by mass.

[0176] 2. Preparation of polyurea modified ternary cathode materials

[0177] The internal temperature of the plowshare dryer cavity was maintained at 110°C by circulating heating oil, the spindle speed was set to 100r / min, the intermediate sample of the ternary cathode material was added to the reaction liquid and stirred for 30 minutes, and then the internal temperature of the plowshare dryer cavity was maintained at 30°C by lowering the temperature of the circulating heating oil, the spindle speed was set to 50r / min, the stirring reaction time was continued for 1 hour, and after cooling to room temperature, the polyurea modified ternary cathode material was sieved and demagnetized; in the above preparation method, the mass ratio of the ternary cathode material to the reaction liquid was 1:0.17; the reaction liquid was obtained by stirring and mixing 1,5-naphthalene diisocyanate, α,ω-diisocyanate polyethylene glycol, and acetone in a mass ratio of 1:0.21:0.5.

[0178] Test analysis

[0179] Under the condition of the same active material ratio, corresponding ternary lithium-ion batteries were prepared using the modified ternary positive electrode materials prepared in the comparative example and the embodiment, respectively, and were marked as test examples 1 to 5 and comparative test examples 1 to 3.

[0180] The other materials, dosages and battery preparation methods of ternary lithium-ion batteries are the same except for the positive electrode materials. The preparation method of ternary lithium-ion batteries is as follows: the modified ternary positive electrode materials prepared in the examples and comparative examples are used as positive electrode active materials, respectively, with the conductive agent carbon black and the binder polyvinylidene fluoride in a mass ratio of 90:5:5, and N-methyl pyrrolidone is used as a dispersant to stir and mix evenly, and then evenly coated on aluminum foil, cut into 8mm diameter positive electrode discs after drying, and transferred to a 120℃ vacuum oven for drying for 24h. The prepared positive electrode disc is used as the working electrode, the metal lithium sheet is used as the counter electrode, and 1mol / LLiPF6 is dissolved in a mixed solution of ethylene carbonate and dimethyl carbonate (wt%=1:1) as the electrolyte, and assembled into a 2032 type button battery in a glove box. The electrochemical performance is tested in the range of 2.8 to 4.2V cut-off voltage.

[0181] (1) Battery rate retention test: Charge from 2.8V to 4.2V at 1C constant current, maintain 4.2V constant voltage charging, cut-off current 0.05C; then discharge to 2.8V at 1C and 3C respectively, and record the discharge capacity retention rate at different rates at -30℃ in turn. The test data are recorded in Table 1;

[0182] (2) Powder resistivity test: A four-electrode powder resistance meter was used to test the powder resistance at the same pressure and different temperatures. The test data are recorded in Table 1.

[0183] (3) SEM test: The positive electrode materials prepared in Example 1 and Comparative Example 1 do not need to be subjected to gold spraying treatment. The microscopic morphology is directly photographed using a field emission scanning electron microscope. The photographing results are shown in Figure 1 and Figure 2 .

[0184] Table 1

[0185]

[0186] from Figure 1 and Figure 2 It can be seen that the high-performance positive electrode material prepared in the embodiment is compared with the positive electrode material prepared in comparative example 1, and its polyurea-modified aluminum hydroxide / poly (TA) composite layer is evenly and effectively coated on the surface of the positive electrode material, which can effectively improve the lithium diffusion coefficient of the material at low temperature, reduce the polarization internal resistance of the prepared lithium-ion battery at low temperature, and show excellent high-rate charge and discharge performance under low temperature conditions.

[0187] From the rate performance test data in Table 1, it can be seen that the capacity retention rates of 1C and 3C of test examples 1 to 5 under low temperature conditions (-30°C) are both higher than 90%, showing excellent low-temperature charge and discharge performance compared to comparative test examples 1 to 3. In addition, from the powder resistivity test results under the same pressure, it can be seen that the resistivity of test examples 1 to 5 at different temperatures is significantly lower than that of comparative test examples 1 to 3, which indicates that the polyurea-modified aluminum hydroxide / poly (TA) composite layer effectively improves the lithium diffusion coefficient at low temperatures and reduces the polarization internal resistance of lithium-ion batteries at low temperatures.

[0188] From the above test results, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0189] The polyurea-modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material prepared by the present invention effectively improves the lithium diffusion coefficient at low temperature, reduces the polarization internal resistance of the lithium ion battery at low temperature, and the battery exhibits excellent high-rate charge and discharge performance under low temperature conditions.

[0190] The present invention has been described in detail above. It will be apparent to those skilled in the art that the present invention may be implemented in a wide range under equivalent parameters, concentrations and conditions without departing from the spirit and scope of the present invention and without the need for unnecessary experimentation. Although the present invention provides specific embodiments, it should be understood that further improvements may be made to the present invention. In short, according to the principles of the present invention, this application intends to include any changes, uses or improvements to the present invention, including changes made by conventional techniques known in the art that depart from the scope disclosed in this application. Applications of some of the basic features may be made within the scope of the following appended claims.

Claims

1. A method for preparing a modified ternary cathode material, characterized in that: The preparation method comprises the following steps: 1) mixing a ternary precursor, a cobalt hydroxide-coated ternary precursor, a dopant, and a lithium source, and sintering the mixed material to obtain an intermediate sample of a ternary positive electrode material; 2) coating the surface of the intermediate sample of the ternary cathode material in step 1 with aluminum hydroxide, then reacting it with thioctic acid (TA) in the first step, and then adding solvent I to carry out the second step reaction to obtain an aluminum hydroxide / poly (TA) composite layer coated ternary cathode material; the solvent I is selected from at least one of dichloromethane, methanol, and chloroform; 3) subjecting the aluminum hydroxide / poly (TA) composite layer coated ternary cathode material described in step 2 to low-temperature oxygen plasma surface treatment to obtain a modified aluminum hydroxide / poly (TA) composite layer coated ternary cathode material; 4) The modified aluminum hydroxide layer and the poly (TA) film layer composite layer coated ternary positive electrode material described in step 3 are polymerized with diisocyanate and α, ω-diisocyanate polyethylene glycol to obtain a polyurea-modified aluminum hydroxide / poly (TA) composite layer coated modified ternary positive electrode material, which is the modified ternary positive electrode material.

2. The preparation method according to claim 1, characterized in that: In step 1), the chemical formula of the ternary precursor is Ni x Co y M 1-x-y (OH)2, wherein 0<x<1, 0<y<1, 1-xy>0, and M is at least one of Mn and Al; And / or, in step 1), the lithium source is at least one of lithium hydroxide, lithium perchlorate, lithium hexafluorophosphate, and lithium carbonate; And / or, in step 1), the dopant is at least one of tungstic acid, tungsten oxide, strontium carbonate, strontium oxide, aluminum oxide, zirconium oxide, niobium oxide, boric acid, vanadium dioxide, and molybdenum trioxide.

3. The preparation method according to claim 1, characterized in that: In the step 1, the particle size of the ternary precursor ranges from 1.2 to 9 μm; And / or, in step 1, the particle size of the cobalt hydroxide-coated ternary precursor is in the range of 1.3 to 6.8 μm.

4. The preparation method according to claim 1, characterized in that: In the step 1, the preparation method of the cobalt hydroxide coated ternary precursor comprises the following steps: taking the ternary precursor dust collection material and the coating agent I and adding them into a stirred reactor filled with deionized water, stirring and mixing at 100 to 300 r / min for 20 to 120 minutes to obtain slurry I, then adding the precipitant I to the slurry I to adjust the pH value to 9 to 11, aging at 30 to 65° C. for 4 to 16 hours, and then filtering, washing, and drying to obtain the cobalt hydroxide coated ternary precursor.

5. The preparation method according to claim 4, characterized in that: The particle size range of the ternary precursor dust collection material is 1.2 to 6.4 μm; And / or, the coating agent I is cobalt sulfate; And / or, the mass ratio of the ternary precursor dust collecting material, the coating agent I, and the deionized water is 1:0.01-0.05:3-5; And / or, the precipitant I is ammonia water and / or sodium hydroxide.

6. The preparation method according to claim 1, characterized in that: In the step 1, the mass ratio of the ternary precursor, the cobalt hydroxide-coated ternary precursor, the dopant, and the lithium source is (0.3-1):3:(0.0001-0.012):(1.43-1.92); And / or, in step 1, the sintering is carried out in a kiln, and the internal pressure of the kiln is set to 200-500 Pa during the sintering; the sintering temperature is 700-950° C., and the sintering time is 10-30 hours.

7. The preparation method according to claim 1, characterized in that: In the step 1, the percentage of the total number of particles W1 with a particle size of 1.2 to 2.9 μm in the intermediate sample of the ternary positive electrode material to the total number of particles W0 is 20.8 to 31.2%; And / or, in step 1, the particle size distribution dispersion of the intermediate sample of the ternary positive electrode material is 2.4 to 4.

8. The preparation method according to claim 1, characterized in that: In the step 2, the aluminum hydroxide coating method includes the following steps: adding the intermediate sample of the ternary positive electrode material and the coating agent II into a stirred reactor filled with deionized water, stirring and mixing at 400-800 r / min for 60-120 min to obtain slurry II, then adding a precipitant II to the slurry II to adjust the pH value to 9-11, aging at 40-75°C for 2-12 h, and then filtering, washing, and drying to obtain the slurry.

9. The preparation method according to claim 8, characterized in that: The mass ratio of the intermediate sample of the ternary positive electrode material, the coating agent II, and the deionized water is 1:0.03-0.06:5-8; And / or, the coating agent II is aluminum sulfate; And / or, the precipitant II is ammonia water and / or sodium hydroxide.

10. The preparation method according to claim 1, characterized in that: In the step 2, the mass ratio of the aluminum hydroxide coated ternary cathode material intermediate sample, thioctic acid (TA), and solvent I is (2066.46-25756.94): (3.6-25.76): 1; And / or, in step 2, the reaction temperature of the first step reaction is 100-120° C., the stirring speed is 50-100 r / min, and the stirring reaction time is 2-6 h; the stirring reaction time of the second step reaction is 30-60 min.

11. The preparation method according to claim 1, characterized in that: In step 3, the low-temperature oxygen plasma surface treatment is performed in a low-temperature plasma surface treatment machine. Before the treatment, the low-temperature plasma surface treatment machine needs to be evacuated, and then oxygen is introduced into the treatment machine to reach the required treatment pressure; The vacuum degree of the vacuum pumping is 5-10Pa; the processing pressure is 20-100Pa.

12. The preparation method according to claim 1, characterized in that: In step 3, the low-temperature oxygen plasma surface treatment step is: setting the frequency of the low-temperature oxygen plasma surface treatment machine to 10-40 Hz, setting the input power to 200-800 W, fixing the spray gun mouth to 10-15 mm from the sample, and using a bow-shaped reciprocating treatment for 5-25 seconds.

13. The preparation method according to claim 1, characterized in that: In the step 4, the polymerization is carried out in a reaction solution, and the reaction solution is obtained by stirring and mixing the diisocyanate, the α,ω-diisocyanate polyethylene glycol and the solvent II in a mass ratio of 1:0.21 to 0.34:0.5; In the step 3, the mass ratio of the modified aluminum hydroxide / poly (TA) composite layer coated ternary positive electrode material to the reaction solution is 1:0.17-0.

24.

14. The preparation method according to claim 13, characterized in that: The α,ω-diisocyanate polyethylene glycol has the following structural formula: 500≤n≤1000; And / or, the diisocyanate is at least one of toluene diisocyanate, diphenylmethane diisocyanate, and 1,5-naphthalene diisocyanate; And / or, the solvent II is acetone and / or N,N-dimethylformamide.

15. The preparation method according to claim 1, characterized in that: In step 4, the polymerization reaction is a two-step temperature polymerization, that is, a stirring reaction is first performed, and a second stirring reaction is performed after the reaction temperature is lowered; the first stirring reaction and the second stirring reaction are both performed in a coulter dryer; The primary stirring reaction is to keep the internal temperature of the coulter dryer cavity at 110-130°C by using a heat transfer medium, set the spindle speed to 100-200r / min, and the reaction time to 30-60min; The secondary stirring reaction is to keep the internal temperature of the coulter dryer cavity at 30-50° C. by using a heat transfer medium, set the main shaft speed to 50-100 r / min, and the reaction time to 1-2 h.

16. The modified ternary positive electrode material prepared according to the method according to any one of claims 1 to 15.

17. A lithium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The material of the positive electrode includes the modified ternary positive electrode material according to claim 16.

Citation Information

Patent Citations

  • Ternary positive electrode material complex precursor for lithium battery and preparation method of ternary positive electrode material complex precursor

    CN108649215A

  • High-nickel ternary positive electrode material and preparation method thereof

    CN111244397A

  • Flexible polymer coated modified ternary positive electrode material and preparation method and application thereof

    CN116826048A

  • Preparation method and application of lithium battery positive electrode material with nanoscale elastomer molecular protective layer

    CN117154036A

  • Secondary battery, battery pack, and vehicle

    EP3297086A1